2017
DOI: 10.1210/jc.2016-3716
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Activation by Steroid Sulfatase Increases Colorectal Cancer Proliferation via GPER

Abstract: Context:Estrogens affect the incidence and progression of colorectal cancer (CRC), although the precise molecular mechanisms remain ill-defined.Objective:The present study investigated prereceptor estrogen metabolism through steroid sulphatase (STS) and 17β-hydroxysteroid dehydrogenase activity and subsequent nongenomic estrogen signaling in human CRC tissue, in The Cancer Genome Atlas colon adenocarcinoma data set, and in in vitro and in vivo CRC models. We aimed to define and therapeutically target pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 44 publications
(56 reference statements)
1
55
0
Order By: Relevance
“…The results showed no significant alteration in CTGF gene expression levels ( Figure 10). However, previous experiments in our lab had evidenced that GPER stimulation after E2 and G1 (100nM) treatment leads to CTGF upregulation and elevated protein expression in HCT116 and HT29 cells 37 . The controversy between the results may be due to different passage number of the cells examined.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…The results showed no significant alteration in CTGF gene expression levels ( Figure 10). However, previous experiments in our lab had evidenced that GPER stimulation after E2 and G1 (100nM) treatment leads to CTGF upregulation and elevated protein expression in HCT116 and HT29 cells 37 . The controversy between the results may be due to different passage number of the cells examined.…”
Section: Discussionmentioning
confidence: 65%
“…Previous projects in the lab have shown that steroid sulphatase (STS), the enzyme that converts conjugated oestrogens to their active forms 50 , is significantly upregulated in human CRC tissue leading to increased availability of active oestrogen. Furthermore, the increase in STS activity substantiated greater CRC tumour burden in mouse models 37 . However, the role of oestrogen is regulated apart from their amount and the presence or absence of oestrogen receptors that mediate their action.…”
Section: Gper Is Expressed In Colon Cancer and Colon Adenoma Cellsmentioning
confidence: 86%
See 3 more Smart Citations